2007
DOI: 10.1007/s00403-007-0773-6
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of skin DNA for oligonucleotide array CGH studies: a feasibility study

Abstract: Array-based comparative genomic hybridization (a-CGH) is a promising tool for clinical genomic studies. However, pre-analytical sample preparation methods have not been fully evaluated for this purpose. Parallel sections of normal male human skin biopsy samples were collected and immediately immersed in saline, formalin and a molecular Wxative for 8, 12 and 24 h. Genomic DNA was isolated from the samples and subjected to ampliWcation and labeling. Labeled samples were then co-hybridized with normal reference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…More recently, aCGH, utilizing tens to hundreds of thousands of long 60-mer oligonucleotide probes, provides intragenic resolution at ranges of 6.5–35 kb with sufficient sensitivity to detect intragenic single copy changes ( 17 ). Early reports of application of FFPE samples to the aCGH platform include the comparison of BAC and aCGH analysis of prostate tumors ( 18 ) and failure by multiple parameters on skin biopsy split samples that assessed effects of various fixatives ( 19 ). Sample preparation methods in utilizing FFPE materials are more uneven and difficult to apply to genome-wide assays.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, aCGH, utilizing tens to hundreds of thousands of long 60-mer oligonucleotide probes, provides intragenic resolution at ranges of 6.5–35 kb with sufficient sensitivity to detect intragenic single copy changes ( 17 ). Early reports of application of FFPE samples to the aCGH platform include the comparison of BAC and aCGH analysis of prostate tumors ( 18 ) and failure by multiple parameters on skin biopsy split samples that assessed effects of various fixatives ( 19 ). Sample preparation methods in utilizing FFPE materials are more uneven and difficult to apply to genome-wide assays.…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising, therefore, that alternative formalin-free tissue handling methodologies have been introduced in recent years. We have previously reported our experience with a new, simple and practical, yet standardized, tissue fixation and processing method that preserves histomorphology and protects macromolecules at ambient temperature [ 4 - 9 ]. This method is easily applicable to both clinical and research settings.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding a-chorionic gonadotrophin, early studies suggested that DNA samples obtained from FFPE tissues were uninterpretable because of various errors such as oversaturation and nonuniformity in replicates. 71 Recent advances have surmounted these impediments and even compared these new methods to suggest optimal a-chorionic gonadotrophin platforms. 72 …”
Section: Nucleic Acidsmentioning
confidence: 99%